Taxonomic novelty in Sichuan Province, China: Veronaea polyconidia sp. nov. (Herpotrichiellaceae), a new addition to hyphomycetous fungi - Su, Pengwei; Chen, Yanpeng; Syed, Asad; Bahkali, Ali H.; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2023)
During an ongoing survey on microfungal diversity in Sichuan Province, China, several specimens of hyphomycetous fungi were collected from decaying branches of Betulaceae plants. Through morphological analysis and a multi-locus phylogenetic study based on the small subunit ribosomal RNA, the internal transcribed spacer, the large subunit ribosomal RNA, and the partial beta-tubulin region, we have identified that these new collections belong to the genus Veronaea, leading us to propose Veronaea polyconidia sp. nov. According to multi-locus phylogenetic analyses, V. polyconidia represents a sister clade to V. botryosa. Morphologically, V. polyconidia is distinct from V. botryosa by its relatively larger conidia and longer conidiophores. Detailed morphological distinctions between the new species and their close relatives are provided. Additionally, the phylogenetic findings in this study, along with morphological comparisons, indicate that V. constricta is conspecific with V. botryosa. Prioritizing the oldest epithet, we have synonymized V. constricta under V. botryosa. These findings not only broaden our understanding of the fungal diversity in Sichuan Province, China but also enhance our comprehension of the broader genus Veronaea.